Faktor pendorong dan dampak negatif pernikahan dini di era modern - Muafiyah, Hanik (Maliki Interdisciplinary Journal, 2024)
Allah SWT emphasizes in the Qur’an that humans were created to live in pairs, as stated in Surah Ar-Rum verse 21. Marriage is a concrete manifestation of Allah’s will which aims to form a harmonious and prosperous family. A harmonious family makes a positive contribution to society by producing individuals who are emotionally and spiritually balanced. However, the phenomenon of early marriage, where marriages are carried out by immature individuals, still occurs frequently. Early marriage carries several risks and negative impacts, including problems with maternal and child health, disruption of education, and economic and social instability. Factors driving early marriage include pregnancy out of wedlock, social and cultural environmental pressures, parental influence, difficult economic conditions, and low levels of education. The negative impacts of early marriage include health complications, disruption of education, instability in marital relationships and economic dependence. Efforts to tackle early marriage include increasing education and awareness, wider access to education, economic empowerment, strict law enforcement, as well as psychological and social support. It is hoped that these steps will reduce the number of early marriages and their negative impacts, as well as create a healthier and more prosperous society.